In situ Estimation of Coral Recruitment Patterns From Shallow to Mesophotic Reefs Using an Optimized Fluorescence Imaging System - Nativ, Hagai; Scucchia, Federica; Martinez, Stephane; Einbinder, Shai; Chequer, Alex; Goodbody-Gringley, Gretchen; Mass, Tali (Frontiers in Marine Science, 2021)
Coral recruitment represents a key element for coral reef persistence and resilience in the face of environmental disturbances. Studying coral recruitment patterns is fundamental for assessing reef health and implementing appropriate management strategies in an era of climate change. The FluorIS system has been developed to acquire high resolution, wide ﬁeld-of-view (FOV) in situ images of coral recruits ﬂuorescence and has proven successful in shallow reef environments. However, up to now, its applicability to mesophotic coral ecosystems remains unknown due to the complexity of the system and the limited time available when working at mesophotic depth. In this study we optimized the FluorIS system by utilizing a single infrared-converted camera instead of the bulkier regular dual-camera system, substantially reducing the system complexity and significantly decreasing the acquisition time to an average of 10 seconds for a set of 3 images. Moreover, the speed-FluorIS system is much more economical, decreasing the cost of the full set-up by roughly 40% compared to the original dual-camera system. We tested the utility of the speed-FluorIS by surveying coral recruits across shallow and mesophotic reefs of the Red Sea (Gulf of Eilat) and Bermuda, two of the most northerly reefs in the world with markedly different substrate and topography, and demonstrate that the modified system enables fast imaging of fluorescence to study coral recruitment patterns over a broader range of depths and reef topographies than previous fluorescence methods. Our single-camera system represents a valuable, non-invasive and rapid underwater tool which will help standardize surveys and long-term monitoring of coral recruits, contributing to our understanding of these vital and delicate early life stages of corals.